A Result of Accidental Noise Pollution: Acoustic Flowmeters Emit 28 kHz Pulses That May Affect Harbor Porpoise Hearing - Schaffeld, Tobias; Schnitzler, Joseph G.; Ruser, Andreas; Baltzer, Johannes; Schuster, Max; Siebert, Ursula (Frontiers in Marine Science, 2022)
Large rivers like the Elbe or the Weser are periodically entered by harbor porpoises of the North Sea. They may even move 97 km upstream to the port of Hamburg, where their presence is highest in spring. This migration is believed to be related to important anadromous prey species travelling upstream for spawning. An acoustic flowmeter in the port of Hamburg emits signals in the hearing range of harbor porpoises. The pulses have a duration of 0.2 ms, a peak frequency of 28 kHz, a source level of 210 dB re 1 µPa and an inter-pulse interval of 4.2 s. The signals are continuously emitted from both sides of the river at a location where the river is 400 m wide. We evaluated the potential of these signals to induce temporary threshold shift (TTS) in harbor porpoise hearing. Hearing tests with a harbor porpoise in human care were conducted to determine TTS onset. We modelled the acoustic field based on underwater noise measurements. The acoustic flowmeters emit pulses in a highly directional beam with a source level high enough for inducing TTS in harbor porpoises by a single exposure up to a distance of approximately 72 m. The received cumulative sound exposure levels for harbor porpoises travelling along the flowmeters are mainly dependent on the timing and distance to the sound source. Accordingly, a close approach to the flowmeter at the time of transmission should be prevented. This could be the case, if vessels force harbor porpoises to displace closer to the flowmeters. We therefore suggest to decrease acoustic flowmeter source levels. This case study emphasizes the need for a mandatory authorization process prior to the use of underwater sound for any purpose with potential effects on aquatic life. Such an authorization process should carefully consider potential effects for target and non-target species.